Public-private sector earnings differentials in a transition economy - Laušev, Jelena (2011)
The aim of this thesis is to analyse how economic transition affected earnings differentials in Eastern European economies. In particular, as the public sector was the sole employer in the pre-transition period, the analysis of public sector pay setting is crucial to understanding how privatisation affected the labour market during the transition.